2021
DOI: 10.1097/mbc.0000000000000983
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of venous thromboembolic events in trauma patients after tranexamic acid administration: an EAST multicenter study

Abstract: To determine if there is a significant association between administration of tranexamic acid (TXA) in severely bleeding, injured patients, and venous thromboembolism (VTE), myocardial infarction (MI), or cerebrovascular accident (CVA). A multicenter, retrospective study was performed. Inclusion criteria were: age 18–80 years old and need for 5 units or more of blood in the first 24 h after injury. Exclusion criteria included: death within 24 h, pregnancy, administration of TXA more than 3 h following injury, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…However, concerns have been raised that indiscriminate widespread adoption might result in TXA administration in the wrong patients, leading to increased morbidity and mortality [6][7][8][9]. Data in the literature have been contradicting, however, with others reporting no significant differences or even decreased adverse effects [10][11][12][13][14]. At present, it remains unclear what the exact mechanism behind TXA is and how it has reduced mortality in CRASH-2 trial, since there was no reduction in packed red blood cells (PRBC) transfusion between patients who received TXA and the ones who did not [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns have been raised that indiscriminate widespread adoption might result in TXA administration in the wrong patients, leading to increased morbidity and mortality [6][7][8][9]. Data in the literature have been contradicting, however, with others reporting no significant differences or even decreased adverse effects [10][11][12][13][14]. At present, it remains unclear what the exact mechanism behind TXA is and how it has reduced mortality in CRASH-2 trial, since there was no reduction in packed red blood cells (PRBC) transfusion between patients who received TXA and the ones who did not [5].…”
Section: Introductionmentioning
confidence: 99%
“…From those studies, we only included thirty-seven trials for full-text evaluation. Finally, 17 studies were found to be eligible for quantitative analysis [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The details of the selected trials are summarized in Table 1 and Table S1.…”
Section: Characteristics Of Studies Included In the Meta-analysismentioning
confidence: 99%
“…The details of the selected trials are summarized in Table 1 and Table S1. Among the seventeen studies, four studies were carried out in combat conditions [23,27,29,30], and 13 studies were carried out on civilian injuries [24][25][26]28,[31][32][33][34][35][36][37][38][39]. Three studies were designed as randomized controlled trials [26,28,36].…”
Section: Characteristics Of Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Following the Clinical Randomization of an Antifibrinolytic in Significant Hemorrhage 2 trial (CRASH-2) (3), its use was adopted worldwide for this indication, initially in trauma centers and later in the prehospital setting. In subsequent trials, it has been found beneficial for severely injured casualties suffering from hemorrhagic shock requiring massive transfusions (4, 5).…”
mentioning
confidence: 99%